Virtual Prototyping Application using Computer Aided Engineering in Plastic Product Manufacturing - Ahmad Juang Pratama (Universitas Al Azhar Indonesia, 2011)
Efficiency in using plastic injection technology, especially within small to medium enterprises, is a very difficult target to achieve. One of the contributing factor to the high cost of using this technology is the trial and error nature of constructing the plastic mold which directly affect machninig cost and longet production cycle time. The trial and error scheme can be significantly reduced and even eliminated with the application of concurrent engineering method supported by virtual prototype based CAD (computer aided design) and CAE (computer aided engineering). Virtual prototype technology gives way to product analysis, design and material optimization, and proses parameter optimization prior to implementing the manufacturing process. Therefore, we can anticipate all potential manufacturing flaws during the design process. It is then expeceted to reduce machning and production process cost, increase product quality to boost up Company’s competitive advantage.